Plasma Viscosity: Is a Biomarker for the Differential Diagnosis of Alzheimer's Disease and Vascular Dementia?. (February 2013) - Aras, Sevgi; Tek, Ibrahim; Varli, Murat; Yalcin, Ahmet; Cengiz, Ozlem Karaarslan; Atmis, Volkan; Atli, Teslime
In this study, the importance of plasma viscosity (PV) as a biomarker in differential diagnosis of dementia subtypes especially Alzheimer's disease (AD) and vascular dementia (VaD) was investigated. Our study recruited 45 patients with AD, 35 patients with VaD, and control participants. Individuals with inflammatory disease, infection, heart, liver, renal failure, and with high erythrocyte sedimentation rate and C-reactive protein levels were excluded from the study. The cases underwent comprehensive geriatric assessment. The PV measurements were performed with Brookfield DV-II viscometer. The PV measurements of AD, VaD, and control groups were 1.61 ± 0.08, 1.70 ± 0.06, and 1.48 ± 0.06 mPa S, respectively. The PV levels of the dementia group were significantly higher than the control group ( P < .001). When the dementia group was analyzed by itself, patients with VaD had higher PV levels than the patients with AD ( P < .001). The PV is a biomarker to be used in diagnosis as well as in differentiating between the 2 most common forms of dementia which are AD and VaD.